2022
DOI: 10.3389/fmolb.2022.920727
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the O-GlcNAc Modified Proteome: Applications for Health and Disease

Abstract: O-GlcNAc is a pleotropic, enigmatic post-translational modification (PTM). This PTM modifies thousands of proteins differentially across tissue types and regulates diverse cellular signaling processes. O-GlcNAc is implicated in numerous diseases, and the advent of O-GlcNAc perturbation as a novel class of therapeutic underscores the importance of identifying and quantifying the O-GlcNAc modified proteome. Here, we review recent advances in mass spectrometry-based proteomics that will be critical in elucidating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…(3) How is O-GlcNAcylation regulated in different tissues in physiological and pathophysiological contexts? These questions require advances in detection methods for O-GlcNAcylated sites and cell-specific knock-out models that are being currently developed by different groups [ 159 , 160 , 161 ]. Current detection limitations still delay the development of the protein O-GlcNAcylation field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) How is O-GlcNAcylation regulated in different tissues in physiological and pathophysiological contexts? These questions require advances in detection methods for O-GlcNAcylated sites and cell-specific knock-out models that are being currently developed by different groups [ 159 , 160 , 161 ]. Current detection limitations still delay the development of the protein O-GlcNAcylation field.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to protein phosphorylation, the development of specific antibodies to detect single site O-GlcNAcylation have intrinsic biological limitations (detection of GlcNAc-modified sites by antibodies). Additionally, the detection tools currently being employed are complex and expensive, such as O-GlcNAc labelling followed by mass spectrometry analysis [ 159 ]. Recent advances such as chemical reporters and biorthogonal reactions, however, are promising strategies to foster future protein O-GlcNAcylation studies [ 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…O-GlcNAc glycosylation modification is widely involved in many cells’ life processes, such as cell cycle, gene transcription, protein translation and processing, and signal transduction. Abnormal modification of O-GlcNAc glycosylation occurred in many diseases [ 42 ]. Studies have confirmed that OGT is highly expressed in liver tumors [ 43 ], colon tumors, bladder cancer, and breast cancers [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…O -GlcNAcylation is extremely common, generally underappreciated, and catalyzed within the cytoplasm by a single enzyme, O -GlcNAc transferase (OGT). 15 This modification appears to have fairly rapid on/off rates and competes with phosphorylation at the same or adjacent sites creating a means of intracellular signaling. 16 …”
Section: Oligosaccharide Structure and Biosynthesismentioning
confidence: 99%